2021
DOI: 10.2147/prbm.s329905
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Friendship is a Blessing in the Exploration of Supervisor Behavioral Integrity, Affective Commitment, and Employee Proactive Behavior – An Empirical Research from Service Industries of Pakistan

Abstract: Purpose Workplace friendships are typically complicated, serving various goals, imposing varying levels of expectation on the members, and representing the interaction among employees. Recent research has highlighted the multifaceted nature of friendship; however, the purpose of this study is to quantify the benefits of friendship at work. The study investigates the impact of supervisor behavioral integrity on employee proactive behavior. Moreover, it constructed a moderated mediation model based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…H 3 proposed the workplace friendship moderating role in the relationship of shared ethical priories and knowledge hiding. The results are consistent with Guohao et al (2021), which posit that there is a certain complication which is created because of workplace friendship (Ingram and Zou, 2008) resultantly, these complications effect the decorum of the organizations as employees goals are differentiated from their organizational goal. H 4 anticipated moderating role of Workplace friendship in the relationship of Lack of shared ethical priorities and knowledge hiding.…”
Section: Discussionsupporting
confidence: 81%
“…H 3 proposed the workplace friendship moderating role in the relationship of shared ethical priories and knowledge hiding. The results are consistent with Guohao et al (2021), which posit that there is a certain complication which is created because of workplace friendship (Ingram and Zou, 2008) resultantly, these complications effect the decorum of the organizations as employees goals are differentiated from their organizational goal. H 4 anticipated moderating role of Workplace friendship in the relationship of Lack of shared ethical priorities and knowledge hiding.…”
Section: Discussionsupporting
confidence: 81%
“…This position implies that employees within Nigeria's work organizations are deterred from engaging in counterproductive meeting behaviors the more they perceive their leaders as having integrity. The current results support [26], which opine employees who perceive their leaders to have integrity tend to engage in positive behaviors than those who less perceive their leaders as such. These results also corroborate the study of [27], which established a negative relationship between perceived leadership integrity and counterproductive meeting behavior.…”
Section: Discussionsupporting
confidence: 76%
“…Through leaders' integrity within a workplace, employees can actively contribute to themselves and the organization by exhibiting several positive behaviors [25]. Employees who perceive their leaders to have integrity tend to engage in positive behaviors than those who less perceive their leaders as such [26]. Their research [27] established a negative correlation between perceived leadership integrity and counterproductive meeting behaviour.…”
Section: Perceived Leadership Integrity and Counterproductive Meeting Behaviormentioning
confidence: 99%
“…The more employees expect integrity in the workplace, the higher the levels of proactive work behaviors because they feel safe towards their subordinates (Spector, 2011). L. Guohao et al (2021) found a positive relationship between integrity and proactive work behavior. So, the hypothesis is as follows.…”
Section: Development Research Hypothesesmentioning
confidence: 95%